Tipologi Pemikiran Hukum Islam: Pergulatan Pemikiran dari Tradisionalis Hingga Liberalis - Muhammad Harfin Zuhdi (Universitas Islam Negeri Mataram, 2012)
Typology of Islamic legal thought is a method to understand the development Islam in the historical reality, and in the context of dynamics and dialectics of interpretation which is strongly associated with the dimensions of space and time. Every Muslim intellectual has its own perspective in understanding the doctrine of his religion, so there are dynamics of struggle of discourse contestation in the Islamic legal thought. This paper aims to elaborate a typology of Islamic legal thought which is categorized into three groups, namely the traditional, moderate, and liberal. The three-categories may represents the struggle of legal thought in the long range of Islamic history.